Epidemiologia dos óbitos neonatais hospitalares associados à asfixia perinatal no interior do Estado de Alagoas em 2009 - Silva, Cicero José da [UNIFESP] (2010)
Objective: To describe epidemiologic frequency and characteristics of intra-hospital neonatal deaths associated to perinatal asphyxia in the country side of Alagoas state in 2009. Method: Prospective cross-seccional study with weekly active search for medical records of mothers and their newborn infants who died before 28 days of age from January 1st to December 31, 2009, in 11 maternity hospitals from 7 towns which account for 67% of newborn births in the country side of Alagoas. This study was approved by the Research Ethics Committee as well as by all the 11 maternity hospitals. It was considered death associated to perinatal asphyxia if at least one of these criteria was found: Apgar score <6 in the 5th minute; meconium aspiration syndrome (MAS); hypoxic-ischemic encephalopathy; Apgar score <3 in the 1st minute with ventilation at birth; death record of hypoxia/asphyxia at birth in the Declaration of Death. Patients with major malformations, birth weight <400g or gestational age <22 weeks were excluded. Descriptive analysis of patients included the variables of location and condition of birth and death, morbidity and therapeutic interventions. Information on physical structure, material and human resources were collected from hospitals in March and September/09. Results: In 2009, in 11 hospitals were registered 19,740 live births and 173 neonatal deaths, 155 were preventable, of which 100 (65%) had birth asphyxia (5.1 deaths per thousand live births) and 91% occurred at the same hospital of birth. Obstetrician and pediatrician were present, respectively, in 83% and 91% of the births of the 53 infants with low birth weight and 77 and 79% of 47 infants 2500g. Apgar score 3 in the 1st minute occurred in 83% of the 53 low birth weight newborn and 1/3 of them had no improvement at 5 minutes score; 92% developed respiratory distress, 46% received surfactant, 70% mechanical ventilation and 73% remained in incubator. Of the 61 infants >2500g, 47(77%) had asphyxia, half of them had 1st minute Apgar score 3 and 17% of whom remained unchanged at 5 min. MAS was clinically diagnosed in 59% of this group, 59% received mechanical ventilation and 56% remained in the incubator. Died outside environment intensive care 34% of low birth weight newborn infants and 62% of 2500g. Death occurred within 24 hours in 41% and between 2 and 6 days in 47% of the 100 newborn infants. Half of death certificates contained reference to asphyxia and no autopsy was performed. In March/2009, in each hospital there was a single neonatal resuscitation table for reception at birth and 7 had complete material for manual ventilation. In evaluating September/09, all tables had material for resuscitation. Two hospitals had neonatal ICU beds and 4 had care intermediate. Between 2007 and 2009, 58% of pediatricians and 25% of staff nursing had done neonatal resuscitation training course. Conclusion: The rate of neonatal deaths with birth asphyxia in the interior of Alagoas is very high (65%), especially in newborns weighing over 2,500g, identifying inadequate conditions of care in delivery rooms and in neonatal care units.